Contradictions of value: between use and exchange in cord blood bioeconomy. Issue 1 (12th April 2012) - Brown, Nik
Abstract: Umbilical cord blood (CB) has become established as an increasingly viable clinical alternative to bone marrow in the treatment of leukaemia leading to the construction of a global network of CB banks promoted through a moral ethos of gift. Additionally, some banks offer the opportunity to retain stem cells privately. CB is discursively presented as clinical 'waste', a 'by‐product' of birthing. In this way CB units are made available to a global exchange‐based bioeconomy. Crucially, CB collection has developed in parallel with several necessary obstetric practices, especially the immediate clamping of the cord following delivery, essential to high volume collection. However, this article strongly suggests the promotional basis of CB banking (such as by gift, waste or donation) is in tension with the growing preference of new parents to delay cord clamping. Based on focus groups with expectant parents, the promotion of CB banking can in fact be seen to feed into critical reflection on the value of CB for newborn infants, potentially reinvigorating a tradition of delayed umbilical cord clamping. Theoretically, these contradictory systems of valuing are conceptualised through recent literature on bioeconomy and Marx's writings on the contrasting tensions between use and exchange value.